Vietnam - Storey, Robert (Lonely Planet, 1997)
Contents: facts about the country; facts for the visitor; getting there and away; getting around; Ho Chi Minh city; around Ho Chi Minh city; Mekong delta; central highlands; south-central coast; Quang Nam and Da Nang; Hue; DMZ and vicinity; ...